Applying the Newman-Peacock Prognostic System to a Portuguese Obstetrical Population - A Useful Tool? - Rita Mendes Silva; Nuno Clode (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2018)
Abstract Background External cephalic version (ECV) is a maneuver that enables the rotation of the non-cephalic fetus to a cephalic presentation. The Newman-Peacock (NP) index, which was proposed by Newman et al. in a study published in 1993, was described as a prediction tool of the success of this procedure; it was validated in a North-American population, and three prognostic groups were identified. Purpose To evaluate the value of the NP score for the prediction of a successful ECV in a Portuguese obstetrical population, and to evaluate maternal and fetal safety. Methods We present an observational study conducted from 1997-2016 with pregnant women at 36-38 weeks of pregnancy who were candidates for external cephalic version in our department. Demographic and obstetrical data were collected, including the parameters included in the NP index (parity, cervical dilatation, estimated fetal weight, placental location and fetal station). The calculation of the NP score was performed, and the percentages of success were compared among the three prognostic groups and with the original study by Newman et al. The performance of the score was determined using the Student t-test, the Chi-squared test, and a receiver operating characteristic (ROC) curve. Results In total, 337 women were included. The overall success rate was of 43.6%. The univariate analysis revealed that multiparity, posterior placentation and a less engaged fetus were factors that favored a successful maneuver (p < 0.05). Moreover, a higher amniotic fluid index was also a relevant predictive factor (p < 0.05). The Newman-Peacock score had a poorer performance in our population compared with that of the sample of the original study, but we still found a positive relationship between higher scores and higher prediction of success (p < 0.001). No fetal or maternal morbidities were registered. Conclusions The Newman-Peacock score had a poorer performance among our population compared to its performance in the original study, but the results suggest that this score is still a useful tool to guide our clinical practice and counsel the candidate regarding ECV.